Force Entrepreneurship in Contemporary Russia. Introduction. Part 1: Organized Crime and Market Forms: Problem Discussion - ВолковВадим Викторович (Journal of Economic Sociology, 2010)
In the first part and in the introduction the author gives the frames for the research of force entrepreneurship in Russia and on the basis of the rich empirical materials and the methodological approach of institutionalism formulates the questions, which will be in the focus of the book. What social-economic conditions led to the quick formation of the organized crime groups and other private force structures? Who became a member of them? What was their activity? What role did they play in the new social-economic order? What is the character of the private force structures’ evolution and how this evolution is linked with the economic market and state setting in Russia?